Comparative Outcome of Three Different Approaches for Supracondylar Humeral Fractures in Children in Khyber Pakhtunkhwa, Pakistan - Muhammad Shakeel, Mohib Ullah Khan, Zia Ullah, Muhammad Afrasiyab Javed Khan, Muhammad Asghar Essa, Afifa Tahir (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The closed reduction and percutaneous pinning are the min treatment approaches tested in pediatric humerus supracondylar fractures but the treatment approach preferred in fractures without closed reduction is remains unclear. Objectives: The purpose of this study was to compare three common orthopaedic procedures for treating children with supracondylar humerus fractures of the displaced extension type. Methods: The current retrospective analytical study was started in the Department of Orthopedic at Khyber Teaching Medical College from 2015 to 2020, with the approval of the clinical research ethics committee. This analysis was conducted on 64 patients between the ages of 1 and 12 years who underwent hospital surgery for Gartland IIb, Gartland IIb, and Gartland III supracondylar humerus fracture. Results: A total of 64, 22 patients were from group A, in which 18 (81.81%) were male and only 4 (18.18%) were female, while in group B and C were 21 (80.76%), 5 (19.23%) and 14 (87.5%), 2 (12.50%) male and female, respectively. The injury on left elbow and right elbow in group A was recorded 68.18 and 31.81%, respectively. Among the total injured children, the left elbow was fractured in 47 (73.43%) case and the right one in 7 (10.93%). Approximately the duration of injury to therapeutic procedure was recorded 7.53±3.03 hours in the study. When compared to the group of displaced supracondylar humeral fractures that were conservatively handled, the functional and aesthetic treatment outcomes between the closed and open reduction with K-wire fixation groups were significantly different. According to this system, excellent, fair, good and poor functional outcomes were recorded in 10 (45.45%), 6 (27.27%), 4 (18.18%) and 2 (9.09%) patients of A group, respectively, while 13 (50%), 5 (19.23%), 5 (19.235), and 3 (11.50%) patients in group B, respectively. The poor and fair functional outcome was noted in 1 (6.25%) and 3 (18.75%) patients, respectively in group C. Practical implication: This is a critical surgical condition in children and they should be provided with the appropriate treatment to acquire the child’s ability of movement. According to our findings among three management techniques, the most favorable was open reduction with K-wire fixation, and therefore was recommended with good success rate. Conclusion: It was thus concluded that open reduction with K-wire fixation is a good alternative to closed reduction with percutaneous pinning for treating displaced pediatric supracondylar humeral fracture. Keywords: Children; Supracondylar humerus fracture; Surgical treatment; Pediatric fractures; Pakistan